Analisis Beban Lentur dan Daya Serap Air pada Genteng Beton : Literatur Review - Mohammad Ali Mahfud Efendi (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Concrete roof tiles are an important material in building construction, particularly for roofing work, due to their advantages in terms of strength, durability, and material availability. This study aims to analyze two main physical characteristics of concrete roof tiles, namely bending load and water absorption, using a literature review approach from various previous studies. Bending load refers to the material's ability to withstand bending forces, while water absorption describes the material's capacity to absorb and store water through its pores. These two properties significantly influence the quality and durability of roof tiles in facing external environmental conditions, especially wet-dry cycles and mechanical loads. The results of the literature review indicate that the use of waste as an aggregate substitute in concrete mixes can significantly improve the performance of concrete roof tiles. For example, research using broken roof tiles and ceramic waste as aggregate substitutes successfully increased flexural strength to a range of 12.5–15.0 MPa. Meanwhile, variations in water absorption were recorded in the range of 4%–8%, depending on the material composition and production method. This proves that the use of recycled materials not only supports sustainability but also improves the mechanical and physical properties of concrete roof tiles. Overall, this study underscores the importance of material innovation in concrete roof tile production, particularly utilizing waste as an alternative aggregate. However, further research is needed to explore the best combination of materials and production techniques for producing high-quality, efficient, and environmentally friendly concrete roof tiles.